POLICY STRATEGY OF VILLAGE COMMUNITY EMPOWERMENT INSTITUTIONS IN AN EFFORT TO INCREASE WELFARE - Rezza Rahman, Muhammad Faizal; Maruapey, Muhammad Husein; Saprudin, (Administratie: Jurnal Administrasi Publik, 2024)
The most important thing about community empowerment is starting with how to create conditions, atmosphere or climate that allows the community's potential to develop. To achieve the goal of empowerment, various efforts through various strategies can be carried out. The government has an important role in encouraging the realization of community welfare, one of which is by providing policies and programs that support community welfare. However, regional governments have an interest in developing BUMDes, because the existence of these institutions is believed to be able to stimulate the economy in rural areas, which of course has a positive impact on development in the region. Through the Village Community Empowerment Institute (LPMD) as an institution authorized in the field of community and village empowerment, the regional government participates in encouraging the development of BUMDes. This research aims to analyze the policy strategies of community empowerment institutions and find out the problems and obstacles to these policy strategies in an effort to improve community welfare in Ciawi District.